Síntese e estudo in sílico de análogos da propafenona e resolução cinética enzimática do acetato de 1-[4-amino-2-(3-fenilpropanoil)fenoxi]-3-cloropropan-2-ila, catalisada por lipases - Lima, Gabriella de Castro (2021)
The preparation of analogs of a specific drug is one of the strategies to reduce its side effects and, possibly, discover new biological activities. In this work, we report the synthesis of four analogs of propafenone, a drug used to treat arrhythmias. The modifications were carried out with the insertion of an amino group in the C-5 phenolic benzene ring and the introduction of alkylamines in the side chain, such as propylamine, isopropylamine, diethylamine and dibutylamine leading to the analogs rac-5a (50%), rac-5b (60%), rac-5c (70%) and rac-5d (40%), respectively. In silico studies revealed that all analogs have a good oral bioavailability, in addition to being in agreement with Lipinski's “rule of 5”. A molecular docking study revealed that the rac-5c analog showed higher affinities than propafenone in relation to beta 1 and beta 2 adrenergic receptors, as well as sodium channels. In parallel, a protocol was developed for the enzymatic kinetic resolution of a key intermediate common to the rac-5a-5d analogs, 1-[4-amino-2-(3-phenylpropanoyl)phenoxy]-3-chloropropan-2-yl acetate (rac-7), via hydrolysis reaction, catalyzed by lipases. After a detailed study of the reaction parameters, rac-7 can be resolved in a 0.1 M solution of 80% phosphate buffer (pH 7) and 20% toluene, at 40 °C for 30 h, with a ratio enzyme/substrate (m/m) of 1:1, in the presence of the Thermomyces lanuginous lipase immobilized on immobead-150 (TLL), leading to chiral chlorohydrin (5) 1-(5-amino-2-(3-chloro-2-hydroxypropoxy)phenyl)-3-phenylpropan-1-one with enantiomeric excess > 99% and the remaining chiral substrate (7) 1-[4-amino-2-(3-phenylpropanoyl) phenoxy]-3-chloropropan-2-yl acetate with 98% enantiomeric excess, 50% conversion and E > 200.